Post-logging regeneration and recruitment of shihuahuaco (Dipteryx spp.) in Peruvian Amazonia: implications for management - Putzel, L.; Peters, C.M.; Romo, M. (2011)
Over the past decade, shihuahuaco timber – comprising several species of Dipteryx (Fabaceae) traded internationally as “cumarú” or “Brazilian teak” – has become one of the most highly demanded types of hardwood from Peruvian Amazonia, particularly in the Chinese market. Dipteryx is an ecologically important canopy-emergent genus with widespread distribution in neotropical forests. To assess the response of Dipteryx to logging, we conducted inventories in three logging areas in the Regions of Ucayali and Loreto, Peru. The size-class distributions of Dipteryx populations in recently logged sites showed that initial post-logging conditions enhance recruitment of residual seedlings. These conditions are created by a combination of logging gaps and the activities of farmers migrating into logged lands. Through protection and liberation of shihuahuaco seedlings in post-logged forest as well as within and around agricultural fields, local residents and timber companies could favor the recovery of this valued resource. However, as logged land is increasingly converted to agriculture and pastureland, the reestablishment of mature seed trees is not assured.